Mating behaviour of the European leafminer Scaptomyza flava (Diptera Drosophilidae) - Shakeel, M.; He, X.Z.; Martin, N.A.; Hanan, A.; Wang, Q. (New Zealand Plant Protection, 2010)
European leafminer Scaptomyza flava (Falln) is an important pest of brassicas peas and gypsophila in New Zealand This study examined the mating behaviour of this species for the first time under laboratory conditions Males were the active sex in the entire mating behavioural sequence involving approaching courting and mounting females and copulation Copulation lasted for about 20 min There was no significant difference in pre courtship courtship and mating durations between virgin and mated males However mated males were significantly more likely to perform courtship and to achieve mating than virgin ones It is suggested that males learn from mating experience which helps them achieve higher mating success Both virgin and mated males tended to disrupt mating couples but could not separate them